Edukasi Tentang Kesehatan Mental pada Remaja di SMA Negeri 1 Rawalo - Mayliza, Amanda Tri; Triana, Noor Yunida; Cahyaningrum, Etika Dewi (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Adolescents are vulnerable to mental health issues due to social pressure, parenting, and environmental factors. Limited awareness and access to mental health services make education essential to enhance their understanding of psychological well-being. Objective: The objective of this community service was to enhance 11th grade students’ knowledge at SMA Negeri 1 Rawalo about mental health, maintaining psychological well-being, and recognizing signs of mental disorders. Method: This program was conducted from June 19–23, 2025, through three stages: preparation, implementation, and evaluation. The method used was interactive lectures supported by PowerPoint, leaflets, and animated videos. Students’ knowledge was assessed using pre- and post-test questionnaires, analyzed descriptively and quantitatively. Result: The average score of students’ knowledge in the pre-test was 62, with most students categorized as fair to poor. After the educational program, the average score increased to 82, with a shift of most students into the good category. This indicates a significant improvement of 32.2%, proving the effectiveness of the applied educational methods. Conclusion: Mental health education through interactive lectures and visual media effectively increased adolescents’ knowledge about mental health. This program serves as a preventive effort to raise awareness and prepare adolescents to face psychological, social, and academic challenges.